STUDI ROCK TYPING PADA RESERVOIR KARBONAT - Feldy Riza, Muhammad
Rock typing is process to classifying reservoir rocks into distinct units, each of which was deposited under similar geological conditions and has undergone similar diagenetic process. The use of rock typing is to characterize the reservoir rock and determine the flow behavior of reservoir rock. The use of reservoir rock typing is very essential in estimation of permeabilitas in uncored well and also in distribution of SCAL properties for reservoir characterization and description. Studies of rock typing have been made by many geoscientist and engineers to understand the reservoir properties and reservoir behavior on the dynamic condition. The most challenging work in rock typing is in classifying rock types for heterogeneous carbonate reservoir. Unlike the homogeneous clastic reservoir, carbonate reservoir may experience different diagenetic process in a single reservoir. Thus, resulting in a more heterogen and complex pore structure and pore geometry than clastic rocks. Common methods in classifying rock types are commonly use the assumptions of homogenous reservoir which having unique ?-k relationship and capillary pressure relationship for a single rock type. Unfortunately, the common rock typing for clastic reservoir cannot universally applied in carbonate reservoir due to the heterogeneousity and complexity of its pore architecture. This paper proposed an integrated method in reservoir rock typing for carbonate using the equation derived from capillary tube model. The proposed methods distinguished rock types from carbonate core samples based on the similarity of pore structure and pore geometry of the rocks. Capillary pressure, pore throat radius, and thin sections data were also used to support the proposed methods. The result shows that the proposed method can give simpler and more accurate method in rock typing in heterogeneous carbonate reservoir.